Avaliação da adaptação marginal e resistência a flexão de estruturas implanto-retidas submetidas a três diferentes técnicas de soldagem - Daroz, Flávio Dias (2016)
The osseointegrated dental implants represent an optimal treatment options for oral rehabilitations, however, the presence of misfits between implant-supported prosthetic structures and the implant abutments may generate severe stresses into the implantsupported system, ultimately causing mechanical and biological failures. To correct the dimensional distortions of the implant prosthetic frameworks caused by the manufacturing process, which produce the marginal misfits, it is necessary to perform a sectioning and soldering process. The main soldering processes reported in the literature are the torch soldering and laser welding. Comparatively, laser welding process produces implant frameworks with reduced marginal misfits, while torch soldering process is able to produce frameworks with high strength values; however, it is largely recognized that both soldering process affect negatively the structural strength as compared to single piece frameworks. A reduced strength of the implant supported frameworks may induce early failures while in service. Therefore, the present study compared the marginal misfits and flexural strength of frameworks submitted a proposed soldering technique that associates electric soldering and torch soldering to frameworks submitted to torch soldering, laser welding and single piece frameworks. The objective of the proposed technique was to produce implant-supported frameworks with reduced marginal misfit and elevated structural strength.